The advantages of using photonic crystal fibers instead of the conventional fibers in optical gyroscope - Ali Muse, Haider (Eastern-European Journal of Enterprise Technologies, 2015)
In this paper we proposed to use of a hollow core photonic crystal fiber 1550nmλ , Ø10 µm instead of the conventional fibers in optical gyroscope .Two beams are again propagating through the fiber in opposite directions. Due to the Sagnac effect, the beam travelling against the rotation experiences a slightly shorter path delay than the other beam. The resulting differential phase shift is measured through interferometry, thus translating one component of the angular velocity into a shift of the interference pattern which is measured photometrically. Photonic crystal fibers present special properties and capabilities that lead to an outstanding potential for sensing applications according to these features we can elimination a lot of the problems that exist in the conventional fiber optic gyroscope and getting better and more accurate results in the same conditions when using Photonic Crystal Fibers.